Optimization of Advanced Encryption Standard Algorithm (AES) on Field Programmable Gate Array (FPGA) - Jain, Neelesh; Ajnar, D. S.; Jain, P. K. (2019 International Conference on Communication and Electronics Systems (ICCES), 2019)
In this paper, we have proposed high speed Advanced Encryption Standard (AES) hardware architecture by using parallelism in the process. National Institute of Standards and Technology (NIST) cases are predefined inside the module will be selected by test case bits, according to test case bit selection, the key and input will be selected, and module generate corresponding output and clock cycles reduces to 44 cycles. AES Algorithm synthesized using VHDL Code and targeted into FPGA. For Synthesis and Simulation Xilinx Design Suit Version 14.7 is used. The design has been Successfully tested on ARTIX-7 FPGA.